Retrospective Evaluation of Forensic Medicolegal Childhood Deaths Among Children Aged 0-6 Years - Yıldırım, Ali; Polater, Erdoğan; Bütün, Celal (The Bulletin of Legal Medicine, 2020)
Objective:The aim of this study was to analyze the epidemiological pattern and characteristics of forensic cases resulting in death among children aged 0-6 years and to discuss the solution offers in order to prevent such events that may result in death in 0-6 years of childhood. Materials and Methods:73 cases of medicolegal childhood death among children aged 0-6 years whose post-mortem examinations, dead body examinations and/or autopsies were performed at the morgue of the Cumhuriyet University Hospital in a 8-year period between January 1, 2008 and December 31, 2016 were included in the study group and retrospectively analyzed. In all statistics, the SPSS v.20 statistical software was used, and a p value of <0.05 was accepted as statistically significant. Results:The study included 73 forensic cases resulted in death whose dead body examinations and autopsies were performed. Of the cases, 52.1% (n:38) were female and 47.9% (n:35) were male. When the age groups were compared, it was found that the highest mortality rate was in the 0-1 age group with 65.8%. When the manner of death was compared by age groups after autopsy and toxicology/histopathological examinations performed, it was found that the majority of deaths among children aged 0-1 years was due to sudden infant death syndrome with 35.4% (n:17), drowning in water was the most common cause of death between 2-3 years of age with 35% (n:7), followed by accidental deaths due to fall with 30% (n:6), and the deaths among children aged 4-6 years was due to traffic accident...